Structural, Optical and Electrochromic Properties of Sol–Gel V2O5 Thin Films - M. Benmouss; A. Outzourhit; R. Jourdani; A. Bennouna; E. L. Ameziane (Active and Passive Electronic Components)
Vanadium pentoxide thin films are prepared by the sol–gel route by dissolving V2O5 powder (99.5% purity) in H2O2 solution. The solution is spin-coated on glass substrates for optical (UV–VIS–NIR) and XRD analysis, and on ITOcoated glass substrates for electrochromic measurements. The samples are then annealed at 150°C for 1 hour. The resulting films have a yellow-orange color, typical of polycrystalline V2O5. XRD measurements have shown that after annealing in air at 400°C the structure of the films has a c-axis preferred orientation, the (0 0 1)-type planes lying parallel to the substrate. SEM analysis revealed a smooth surface. The films’ optical and physical constants (n, α, Eg, the thickness d and the mean thickness inhomogeneity s) are calculated using a simple and accurate method based on the transmission spectrum alone. The films’ electrochromism is studied using cyclic voltammetry (CV) and chronoamperometry in propylene carbonate solution containing 1 mol/l LiCIO4. The films show reversible multichromism (yellow–green–blue) upon Li+ ion insertion/extraction. The absorbance of films colored at three different potentials is measured in the UV–VIS–PIR wavelength range, and this study shows that the changes in the optical absorption are consistent with the film color changes. Finally, the optical and electrochromic properties of the films prepared by this method are compared with those of our sputtered films already studied and with other works.